Identification of In Vivo Metabolites of Dictamnine in Mice Using HPLC-LTQ-Orbitrap Mass Spectrometry - Yudong Fu; Yujie Deng; Qing Yu; Xuxia Meng; Dabo Wang; Pei Wang; Ping Wang (Journal of Analytical Methods in Chemistry)
Dictamnine (4-methoxyfuro[2,3-b]quinolone, DIC), a common furoquinoline alkaloid in the family of Rutaceae, showed diverse biological activities. To investigate the in vivo metabolic pathways of DIC, metabolism of DIC in mice was studied using a high-performance liquid chromatography coupled to electrospray ionization of hybrid linear trap quadrupole orbitrap (HPLC-LTQ-Orbitrap) mass spectrometer. Nine metabolites were identified in the DIC-treated mouse urine, plasma, and fecal samples, of which two were identified as new metabolites. The major metabolic pathways of DIC in animal and human liver microsomes were confirmed in the present study, including o-demethylation, monohydroxylation, N-oxidation, and 2,3-olefinic epoxidation pathways. For the first time, a mono-acetylcysteine conjugate of DIC (M9) was detected from DIC-treated mouse urine and plasma samples, and 4-methoxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acid (M10) and 2-(2,8-dihydroxy-4-methoxyquinolin-3-yl)acetaldehyde (M11) were identified as new metabolites of DIC; furthermore, using an in vitro human fecal incubation model, furo[2,3-b]quinolin-4-ol (M1) was verified to be a microbial demethylated metabolite of DIC. Collectively, the present study provided new information on the in vivo metabolic fate of DIC.